XoveTIC 2018 - Javier Pereira (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
[This issue of Proceedings gathers papers presented at XOVETIC2018 (A Coruña, Spain, 27-28 September 2018), a conference with the main goal of bringing together young researchers working in big data, artificial intelligence, Internet of Things, HPC (high-performance computing), cybersecurity, bioinformatics, natural language processing, 5G, and others areas from the field of ICT(Information Communications Technology), and offering a platform to present the results of their research to a national audience in the north of Spain. This first edition aims to serve as the basis of this event, which will be consolidated over time and acquire international projection. The conference is co-funded by Xunta de Galicia and European Union. European Regional Development Fund (ERDF).]